Effect of The Brand Image, Promotion, And Service Quality on The Customer Credit Decisions PT. BNI Tbk Iskandar Muda Branch Medan - Jupan Rio Simangunsong; Rahmat Alamsyah Harahap (CERED Indonesia Institute, 2022)
The methods of collecting data with interviews, questionnaires, and documentation studies. The analysis method is multiple linear regression with classical assumption testing, namely normality, multicollinearity, and heteroscedasticity. The research population was 343 customers, the sample with simple random sampling was 185 customers and 30 respondents were tested for validity and reliability. The conclusion of the effect of the brand image, promotion, and service quality simultaneously (F Test) has a positive effect on credit decisions of F count 22.085 > F table 2.65 with a sig. of 0.000 < 0.05. Partially (t-test) the brand image of t count 1.949 < t table 1.973 and a sig. of 0.053 > 0.05, the promotion of t count 3.931 > t table 1.973 and a sig. of 0.000 < 0.05, the service quality of t count 3.228 > t table 1.973 and a sig. of 0.001 < 0.05. The results of the determination coefficient test Adjusted R Square of 0.256, means that the brand image, promotion, and service quality affect the customer credit decisions with a level of 25.6%, while the remaining 74.4% is due to other factors, such as bank interest rates, tenors, and the location where the bank is located.